Effectuer une transition professionnelle pour donner un sens à sa vie - Claire Duchesne (Recherches en Éducation)
This paper examines the process of transitioning to a new profession to give meaning to one’s life. Self-actualization, and especially the concept of individuation, will be reviewed in light of teaching as a second career choice. The paper will present the results of a qualitative study involving eight professionals in transition who have completed an elementary-school teacher education program in the province of Ontario, Canada. Data from the interviews reveal how teaching adds meaning to the participant’s lives. A summary of the data analysis will be presented, and the support system needed for the induction of second career teachers will also be discussed.